The Effects of Asprosin on Exercise-Intervention in Metabolic Diseases - Liu, Lifei; Liu, Yuhao; Huang, Mei; Zhang, Miao; Zhu, Chenyu; Chen, Xi; Bennett, Samuel; Xu, Jiake; Zou, Jun (Frontiers in Physiology, 2022)
Fibrillin is the major constituent of extracellular microfibrils, which are distributed throughout connective tissues. Asprosin is derived from the C-terminal region of FBN1 gene encoding profibrillin that undergoes cleavage by furin protein. In responds to fasting with low dietary glucose, asprosin is released as a secreted factor from white adipose tissue, and transfers to the liver and mediates glucose release into the blood circulation. Through binding to OLFR734, an olfactory G-protein-coupled receptor in liver cells, asprosin induces a glucogenic effect to regulate glucose homeostasis. Bioinformatics analyses revealed that FBN1 gene is abundantly expressed in human skeletal muscle-derived mesoangioblast, osteoblast-like cell, and mesenchymal stem cell, indicating that the musculoskeletal system might also play a role in the regulation of asprosin expression. Interestingly, recent studies suggest that asprosin is regulated by exercise. This timely review discusses the role of asprosin in metabolism, its receptor signalling, as well as exercise regulation of asprosin. Collectively, asprosin has a vital regulatory effect in the improvement of metabolic diseases by exercise.